Solving N-queen Problem Using Genetic Algorithm by Advance Mutation Operator - Vinod Jain; Jay Shankar Prasad (Institute of Advanced Engineering and Science, 2018)
N-queen problem represents a class of constraint problems. It belongs to set of NP-Hard problems. It is applicable in many areas of science and engineering. In this paper N-queen problem is solved using genetic algorithm. A new genetic algoerithm is proposed which uses greedy mutation operator. This new mutation operator solves the N-queen problem very quickly. The proposed algorithm is applied on some instances of N-queen problem and results outperforms the previous findings.